Enabling regional collaborative governance for sustainable recreation on public lands: the Verde Front. Issue 1 (2nd January 2021) - Bettis, Anna; Schoon, Michael; Blanchette, Gabrielle
Abstract : Collaborative governance approaches have been shown to build trust, reduce conflicts and be more responsive than traditional land management strategies because they incorporate diverse perspectives in the decision-making process. Traditional top-down land management often proves inadequate to address landscape-scale problems that cross jurisdictional borders and to produce sustainable outcomes for affected stakeholders. Collaborative governance is an alternative approach, which engages stakeholders – both civil society and public agencies – in a consensus-driven shared decision-making process. A neutral facilitator who clearly communicates the rules of engagement, participatory inclusiveness as well as opportunities to regularly interact face-to-face and generate small wins are among the key factors that have enabled success in previously studied small-scale collaborative governance arrangements. In this study, a collaborative governance effort within the Southwest United States provides insights into how collaborative outcomes can be achieved on public lands at a regional scale and the differences that makes as compared to past studies at smaller scales. This study used a participatory research approach to produce use-oriented research outcomes in tandem with transdisciplinary practitioners on the ground. Our examination provides a deeper understanding of the factors that enable successful collaborative outcomes to be achieved at a regional scale using a community-driven, transparent process.